Experimental evaluation on a centralized air conditioning system embedded with a split-type air conditioner as a dedicated subcooler - Sukri, Mohamad Firdaus; Sumeru, Kasni; Pramudantoro, Triaji Pangripto; Erham, Eddy; Muliawan, Rizki (Elsevier Ltd, 2021)
Dedicated subcooling (DS) is one of the alternative methods to gain significant performance improvement in the air conditioning (A/C) system. However, DS increases the investment cost and the performance improvement depends on the capacity ratio between the subcooler and the main A/C system (RSM). As compared to previous studies, the present study investigates experimentally the performance of the A/C system equipped with DS at smaller RSM, and justify the economic advantage of the proposed system. The experimental study was conducted at constant outdoor, evaporation, and condensation temperatures of 30, 5, and 40◦C, respectively. The experimental facility consists of a main A/C system with a compressor capacity of 11.25 kW and R22 as a working fluid. The sub-system is a split-type A/C system with compressor capacity of 0.75 kW and R290 as a working fluid. Four parameters; the degree of subcooling, cooling capacity, input power, and coefficient of performance (COP) were investigated. The results showed that the DS decreased the condenser outlet temperature, thus led to an average increase in degree of subcooling by 3.4◦C. Consequently, cooling capacity of the main system increased by 1.4 kW, and the input power of the entire system (power consumed by the main and subcooler systems) decreased by 0.4 kW. As a result, the COP raised by 7.8%, as compared to system without DS. In the economic point of view, the analysis showed that the system with DS is economically viable and has a huge potential due to short payback period of just 11.81 months.